2012
DOI: 10.5194/isprsarchives-xxxix-b1-561-2012
|View full text |Cite
|
Sign up to set email alerts
|

Pleiades-Hr Image Quality Commissioning

Abstract: ABSTRACT:PLEIADES is the highest resolution civilian earth observing system ever developed in Europe. This imagery program is conducted by the French National Space Agency, CNES. It operates since 2012 a first satellite PLEIADES-HR launched on 2011 December 17th, a second one should be launched by the end of the year. Each satellite is designed to provide optical 70 cm resolution coloured images to civilian and defence users. The Image Quality requirements were defined from users studies from the different spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Due to its high level of agility and the high performance of the guidance algorithms, the satellite is capable of targeting images along any ground direction within 47° of vertical viewing position, and even more, with very low maneuver durations between two consecutive images [1]. This high agility permits: • to ensure a good reactivity of the system in order to satisfy the urgent needs of the defense or the civil securities • to minimize scheduling conflicts within the dual use framework, and therefore better meet the simultaneous needs of all users • to acquire images in any direction which will allow, for example, coastlines or river routes to be monitored, which could be very useful for optimizing programming in a crisis case (flooding, tsunami, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high level of agility and the high performance of the guidance algorithms, the satellite is capable of targeting images along any ground direction within 47° of vertical viewing position, and even more, with very low maneuver durations between two consecutive images [1]. This high agility permits: • to ensure a good reactivity of the system in order to satisfy the urgent needs of the defense or the civil securities • to minimize scheduling conflicts within the dual use framework, and therefore better meet the simultaneous needs of all users • to acquire images in any direction which will allow, for example, coastlines or river routes to be monitored, which could be very useful for optimizing programming in a crisis case (flooding, tsunami, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition angles (and B/H ratios) are not fixed (as in ALOS-PRISM), but depend on the size of the target area, the orbit, and customer requirements. Beside the investigations carried out by CNES team (Lebègue et al, 2012), very few publications on the evaluation of the Pleiades images can be found in literature at the time of writing (April 2013), due to the novelty of the mission. In particular the potential of the tri-stereo acquisition mode for 3D information extraction is an interesting topic, due to the increasing need of accurate DSM on any point of the globe and with high revisit time, for applications in change and disaster monitoring (Poli and Caravaggi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pleiades-1(A&B) has the capability to acquire stereo imagery in one pass, with a few second differences. It also has ability to provide stereo-pairs color images with 20 km swath width and 70 cm resolution obtained with base-to height ratio from 0.15 to 2 (Lebègue, 2012). The Pleiades has been placed on the same sunsynchronous orbit at 694 km.…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…The Pleiades has been placed on the same sunsynchronous orbit at 694 km. It has been acquiring the panchromatic stereo images with resolution of 50 cm and multispectral images with resolution 200cm and also in bundle form 50 cm black and white and 200 cm multispectral (Lebègue, 2012). The Pleiades satellite has high resolution and low weight and also low cost for acquiring the images of small area.…”
Section: Proposed Frameworkmentioning
confidence: 99%